(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
This project aimed to determine the impact of educational processes mediated by virtual educational pla-tforms in some classroom methodology courses, using bLearning or blended learning process. Based on this, it was proposed to show the status of virtual education at the University of Quindío. A deep study carried out with the students measured their sensitivity towards eLearning, using the Moodle learning platform and a study on the domain of computer tools by teachers, using a random sample of 144 teachers determined the use of technological tools as a support to academic work in 2010. Also, there was created a working and experimentation group, with 18 teachers responsible for22 courses attended by 600 students. This collected information along with the preferences and vision of the students provided an over-view of how the virtual processes have been developed at the University. The product of this investigation, 22 courses in the Moodle platform, allowed us to know the needs of trai-ning and skills in virtual learning environments for teachers and students who participated. Besides, it was demonstrated that it is possible to strengthen the teaching and learning processes and communication through the implementation of B-Learning.